Pengaruh Media Alphabet Fishing Terhadap Kemampuan Membaca Anak Usia 5-6 Tahun Di TK Mawar Putih Kecamatan Singingi Hilir Kabupaten Kuantan Singingi - Nora Fatmawati Ningrum; Nurlita Nurlita; Defni Satria (Journal on Education, 2023)
The ability to read is one of the most important aspects of language, the introduction of reading skills needs to be stimulated in children from an early age, stimulating children's reading abilities from an early age can help children to recognize letters, add new vocabulary and most importantly can make it easier for children to learn. The Alphabet Fishing game can be a simple game designed to help children aged 5-6 years recognize letters. This study aims to determine the effect of Alphabet Fishing media on the reading ability of children aged 5-6 years at Mawar Putih Kindergarten, Singingi Hilirr District, Kuantan Singingi Regency. The type of research used was experimental, using a pre-experimental research design model of one group pretest posttest design, namely research conducted in one group. The data analysis technique used in this study used a t-test using the SPSS Windows Version 25 program. The results of this study indicate that there is a significant effect of using Alphabet Fishing media on the reading ability of children aged 5-6 years in Mawar Putih Kindergarten, Singingi Hilir District. Kuantan Singingi, comparison of the results of the ability test of children before and after the implementation of the experiment by giving treatment in the form of Alphabet Fishing media. The magnitude of the effect is equal to 75,7%, and based on the Normalized Gain assessment criteria it is in the high category.